The Investigation Of Establishing The National Damage Criteria For Blast-induced Ground Vibrations In Turkey - Abdulkadir Karadogan; Ali Kahriman; Umit Ozer; Gungor Tuncer (International Society of Explosives Engineers, 2010)
The environmental problems such as vibration, and air blast are often faced, and discussed on mining, quarrying, civil constructions, shaft-tunnel, pipeline, and dam operations where blasting is inevitable. It is necessary to establish national standards towards to minimize the environmental problems induced by blasting and judicial matters in our country as it is in USA, EU countries and the other developed countries. This necessity and the obligatory of accepting the European Union criteria for Turkey that has started the procedure of joining to EU emphasize the importance of this study. In other words, the establishment of a particular national standard related with this subject is inevitable for Turkey. This will be possible only by studying, applying scientific methods and techniques by the experts.